Toxicity Evaluation of the Naphthalen-2-yl 3,5-Dinitrobenzoate: A Drug Candidate for Alzheimer Disease - Fareeha Anwar; Fareeha Anwar; Uzma Saleem; Atta-Ur Rehman; Bashir Ahmad; Matheus Froeyen; Muhammad Usman Mirza; Lee Yean Kee; Iskandar Abdullah; Sarfraz Ahmad (Frontiers Media S.A., 2021)
The presented study was designed to probe the toxicity potential of newly identified compound naphthalen-2-yl 3,5-dinitrobenzoate (SF1). Acute, subacute toxicity and teratogenicity studies were performed as per Organization of economic cooperation and development (OECD) 425, 407, and 414 test guidelines, respectively. An oral dose of 2000 mg/kg to rats for acute toxicity. Furthermore, 5, 10, 20, and 40 mg/kg doses were administered once daily for 28 days in subacute toxicity study. Teratogenicity study was performed with 40 mg/kg due to its excellent anti-Alzheimer results at this dose. SF1 induced a significant rise in Alkaline Phosphatases (ALP), bilirubin, white blood cells (WBC), and lymphocyte levels with a decrease in platelet count. Furthermore, the reduction in urea, uric acid, and aspartate transaminase (AST) levels and an increase in total protein levels were measured in subacute toxicity. SF1 increased spermatogenesis at 5 and 10 mg/kg doses. Teratogenicity study depicted no resorptions, early abortions, cleft palate, spina bifida and any skeletal abnormalities in the fetuses. Oxidative stress markers (Superoxide dismutase (SOD), Catalase (CAT), and glutathione (GSH) were increased in all the experiments, whereas the effect on melanoaldehyde Malondialdehyde (MDA) levels was variable. Histopathology further corroborated these results with no change in the architectures of selected organs. Consequently, a 2000 mg/kg dose of SF1 tends to induce minor liver dysfunction along with immunomodulation, and it is well below its LD50. Moreover, it can be safely used in pregnancy owing to its no detectable teratogenicity.